DoJ starts probe on Dengvaxia criminal cases. IN News [column] - Requejo, Rey E. (2018)
The Department of Justice will start its preliminary investigation on the criminal charges against former Health secretary Janette Garin and other incumbent and former Health officials filed by families of students who allegedly died after being inoculated with the controversial anti-dengue Dengvaxia vaccine.
Keywords: Dengvaxia